Low-cost copper complexes as p-dopants in solution processable hole transport layers - Kellermann, Renate; Taroata, Dan; Maltenberger, Anna; Hartmann, David; Brabec, Christoph; Schmid, Guenter (Applied Physics Letters, 2015)
We demonstrate the usage of the Lewis-acidic copper(II)hexafluoroacetylacetonate (Cu(hfac)2) and copper(II)trifluoroacetylacetonate (Cu(tfac)2) as low-cost p-dopants for conductivity enhancement of solution processable hole transport layers based on small molecules in organic light emitting diodes (OLEDs). The materials were clearly soluble in mixtures of environmentally friendly anisole and xylene and spin-coated under ambient atmosphere. Enhancements of two and four orders of magnitude, reaching 4.0×10-11 S/cm with a dopant concentration of only 2mol% Cu(hfac)2 and 1.5×10-9 S/cm with 5mol% Cu(tfac)2 in 2,2′,7,7′-tetra(N,N-ditolyl)amino-9,9-spiro-bifluorene (spiro-TTB), respectively, were achieved. Red light emitting diodes were fabricated with reduced driving voltages and enhanced current and power efficiencies (8.6lm/W with Cu(hfac)2 and 5.6lm/W with Cu(tfac)2) compared to the OLED with undoped spiro-TTB (3.9lm/W). The OLED with Cu(hfac)2 doped spiro-TTB showed an over 8 times improved LT50 lifetime of 70h at a starting luminance of 5000cd/m2. The LT50 lifetime of the reference OLED with PEDOT:PSS was only 8h. Both non-optimized OLEDs were operated at similar driving voltage and power efficiency.
Keywords: Engineering controlled terms: Coated materials; Conducting polymers; Copper; Doping (additives); Hole mobility; Light emitting diodes; Organic light emitting diodes (OLED) Ambient atmosphere; Conductivity enhancement; Dopant concentrations; Hole transport layers; Orders of magnitude; Organic light emitting diodes(OLEDs); Reduced driving voltage; Solution processable Engineering main heading: Copper compounds